Analysis and Performance Improvement of WPT Systems in the Environment of Single Non-Ferromagnetic Metal Plates - Linlin Tan; Jiacheng Li; Chen Chen; Changxin Yan; Jinpeng Guo; Xueliang Huang (Energies, 2016)
Wireless power transfer (WPT) is greatly affected when the transmission channel is surrounded by non-ferromagnetic metallic objects and the alternating magnetic field interacts with the metal conductor, which is more of an issue in wirelessly charged electric vehicle (EV) applications. This paper analyses the performances of a WPT system in an environment with a non-ferromagnetic metal plate. The impedance model of the WPT system in the metal environment is established. Moreover the variation law of a coil’s equivalent inductance and resistance is deduced when the coil is surrounded by the non-ferromagnetic metal plate. Meanwhile, simulations, theory and experiments all confirm that the model is correct. Finally, since the system performance of a wireless charging system is influenced by non-ferromagnetic metals, this paper puts forward a method to improve the performance, that is, to place ferrite cores between the receiving coil and a metal plate. Experiments are carried out to verify the method, and the desired results are achieved.